The Influence of Emotional Intelligence and Motivation Toward Agricultural Extension’s Performance at Agricultural Office of Tanggamus District - Anna Ustina Zainal; Gita Hilmi Prakoso (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2019)
The most forward elements of the bureaucracy, dealing directly with farmers is agricultural extensions. Their presence is very crucial in determining the successful of development activities of farmers. The objectives of this research are (1) to investigate the influence between emotional intelligence and motivation toward agricultural extensions’ performance; (2) to investigate influence of emotional intelligence and motivation partially toward agricultural extension’s performance; (3) to prove that emotional intelligence has a dominant influence compared to motivation toward agricultural extensions’ performance. This survey research was done toward agricultural extensions at Agricultural Office of Tanggamus District. Analytical technique used in this research was multiple regressions to find out the influence of independent variables (X) which was examined simultaneously as well as partially toward dependent variables (Y).Based on the result of F-Test it is proved that independent variables affect significantly toward performance variable (Y), so that the first hypothesis is accepted. In other hand, based on T-test, it is proved that X variables partially affect significantly toward the Y variables so that the second hypothesis is accepted. Independent variables which affect dominantly is motivation variable not emotional intelligence so that the third hypothesis is rejected.Keywords: emotional intelligence, motivation, agriculture extension